The extinction curve : growth and globalisation in the climate endgame - Velden, John van der; White, Rob (Emerald Publishing Limited, 2021)
Global communities have arrived at a critical crossroads. The planet is heating up at a historically unprecedented rate and the ecological conditions sustaining vast species, including our own, are poised at irreversible tipping points. Time is up to avoid climate and ecological catastrophe. In such dire circumstances, 'business as usual' - and by extension 'politics as usual' - can no longer be accommodated. The Extinction Curve charts the dynamics of the economic and social relations driving this perilous climate endgame. Recent economic crises have fractured consent over the consequences of growth and globalisation, and political fracturing is now at a defining moment. Ultra-right nationalism, shaped by the vested interests of a tiny minority at the expense of the global majority, threatens descent into a darker and more fortressed world. In contrast, enhanced progressive and environmental activism presents hope of an alternative course. The 50-year attempt by the mainstream environmental movement to create a greener capitalism has failed to reach the required objectives. This book argues that reversing the extinction curve requires ending the growth pandemic embedded within the core of capitalism as a mode of production and consumption. It maps fresh directions for a democratic social, economic and sustainable ecological transformation in the interests of the global majority and, crucially, demonstrates how this can be achieved.
Includes index.
Keywords: Environmental economics.; Capitalism -- Environmental aspects.; Social evolution.; Business & Economics -- Environmental Economics.; elektronické knihy; electronic books